Evaluation of Ultrasonic and ErCr:YSGG Laser Retrograde Cavity Preparation - de Faria-Junior, Norberto Batista [UNESP]; Tanoymaru-Filho, Mario [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Leonardo, Renato de Toledo [UNESP]; Camargo Villela Berbert, Fabio Luiz [UNESP] (Elsevier B.V., 2009)
Root end cavity preparation techniques aim to create a clean and properly shaped cavity in a short time. Although the use of ultrasonics has been widely recommended, a laser can also be used. This study evaluated the time required and quality of retrograde cavity preparations using ultrasonics or ErCr:YSGG laser. Thirty single-rooted teeth were instrumented, root filled, submitted to apicectomies, and grouped. Root end cavities were prepared by using the following: group 1 (G1): CVD (6.1107-6) ultrasonic retrotips (CVD-Vale, Sao Jose dos Campos, Brazil); group 2 (G2): EMS (DT-060/Berutti) ultrasonic retrotips (EMS, LeSentier, Switzerland); and group 3 (G3): ErCr:YSGG (G6/Waterlase; Biolase Technology, San Clemente, CA) laser tips. The time taken to complete the preparation was recorded. Epoxy resin replicas of the root apices were examined under a scanning electron microscope. The parameters for evaluation were the presence of fractures, and the quality of the preparations. The Waterlase showed the highest mean time for preparation of the root end cavities (p < 0.05), and there was no significant difference between the CVD and EMS groups (p > 0.05). Fractures in the cavosurface angle occurred only in G2. G1 and G2 showed better scores for quality of preparation than G3 (p < 0.05). These results suggest that root end cavities should be prepared by ultrasonic tips. (J Endod 2009;35:741-744)
Keywords: apical surgery; ErCr:YSGG laser; root-end cavity preparation; ultrasonics